High strength and ductility of 34CrNiMo6 steel produced by laser solid forming. Issue 2 (February 2019) - Huang, Chunping; Lin, Xin; Liu, Fencheng; Yang, Haiou; Huang, Weidong
Abstract: Because of the excellent mechanical properties of 34CrNiMo6 steel, it is widely used in high-value components. Many conventional approaches to strengthening-steels typically involve the loss of useful ductility. In this study, 34CrNiMo6 Steel having high strength and ductility is produced by laser solid forming (LSF) with a quenching-tempering (QT) treatment. Tempering of bainite is mainly by solid phase transformation in the previous LSF layers during the LSF process. The stable microstructure of LSF consists of ferrite and fine carbides. The microstructure transfers to tempered sorbite after heat-treatment. The tensile properties of the LSF steel meet those of the wrought standard. The UTS and elongation of LSF sample at 858 MPa, 19.2%, respectively, are greater than those of the wrought. The QT treatment enhanced the ultimate tensile strength and yield strength of the LSF sample. The ultimate tensile strength, yield strength, reduction in area, and elongation of the LSF+QT sample at 980 MPa, 916 MPa, 58.9%, and 13.9%, respectively, are greater than those of the wrought standard. The yield strength of the LSF+QT sample is approximately 1.27 times that of the wrought. The LSF samples failed in a ductile fracture mode, while the LSF+QT samples showed mixed-mode failure. The defects have only a small effect on the tensile properties owing to the excellent ductility of the LSF sample.